Mother's Knowledge About Exclusive Breastfeeding in Toddlers - Dian Meiliani Yuli; Nursyamsi Norma Lala; Yeyen Damanik; Serli Serli (Edukasi Ilmiah Indonesia, 2023)
Growth is an important component in assessing nutritional status and can be used to indicate the health or well-being of individuals and their populations. Growth disruption is still a health problem in Indonesia. This study aims to determine the mother's knowledge about exclusive breastfeeding in toddlers. Quantitative research methods with a descriptive approach. The results showed that 17 respondents were knowledgeable (56.7%). The conclusion is that most respondents have a fairly good knowledge of Exclusive Breastfeeding. This is supported by the level of Repondent Education, which is the level of High School Education. The more a person's level of education is, the easier it is to receive information, so the more knowledge he has